Stabilization of platinum–nickel alloy nanoparticles with a sulfur-doped graphene support in polymer electrolyte membrane fuel cells. Issue 113 (28th November 2016) - Xu, Calvin; Hoque, Md Ariful; Chiu, Gordon; Sung, Teresa; Chen, Zhongwei
Abstract : Post-heat treatment of dealloyed Pt–Ni nanoparticles on sulfur-doped graphene for PEM fuel cell cathode catalysis exhibit greatly improved activity and electrochemically active surface area retention over Pt/C in half-cell conditions. Abstract : Polymer electrolyte membrane fuel cells (PEMFC) are limited by the sluggish oxygen reduction reaction (ORR) at the cathode, necessitating the use of platinum-based catalysts for practical use. However, such catalysts suffer from degradation issues related to the catalyst and the support material that prevent prolonged operation. Sulfur-doped graphene (SG) as a catalyst support material promises high durability with pure Pt, but its contribution to lattice-strained Pt as in bimetallic alloys has not yet been determined. In this work, platinum–nickel alloy nanoparticles with SG are synthesized (denoted as Pt–Ni/SG), then chemically dealloyed (denoted as Pt–Ni/SG-DA) and finally subjected to a post heat treatment (denoted as Pt–Ni/SG-PHT). The prepared catalysts Pt–Ni/SG, Pt–Ni/SG-DA and Pt–Ni/SG-PHT are physically characterized and electrochemically tested in half-cell conditions. Pt–Ni/SG-PHT is found to be superior, exhibiting the highest ECSA and mass activity retention with losses of 27 and 28% respectively after 1500 cycles from 0.05 to 1.3 V vs. RHE in HClO4 . This is compared to a 59% ECSA loss and 69% activity loss for commercial Pt/C under the same conditions. Hence, the strong interaction between the metal particles and sulfur-doped graphene resulting from the annealing process as in Pt–Ni/SG-PHT yields a highly stable electrocatalyst for the ORR.